Consumando spazi centrali e notti urbane: micro-geografie dei giovani a Barcellona e a Napoli - Libera D’Alessandro; Sergi Martinez-Rigol (Bollettino della Società Geografica Italiana)
Developing previous research carried out on retail and consumption geographies of young people in Barcelona and Naples, we will focus on the importance assumed, in the production of the city center, by youth consumption of products, spaces and times (of night and weekend). An in-depht analysis will focus on the role of these urban actors in creating, changing, negotiating and contesting, often in conflict with other actors, the nightscapes of retail and consumption. The transformation of the two neighbourhoods of Raval (Barcelona) and Chiaia (Naples) into districts of consumption and night-time entertainment will be the starting point for a reflection on night-life as field of study in urban geography and by now as an essential area of intervention for urban policies.